Efisiensi Pemanfaatan Radiasi Matahari Padi Unggul Pada Berbagai Konsentrasi N Di Lahan Pasang Surut - Ahdalena Ahdalena; Dewi Erika Adriani; Arief Rakhmad Budi Darmawan (Agroekotek View, 2019)
Rice is a type of food crop that is essential to the greater need for human life in Indonesia. Indonesia as an agrarian country with a large population faces challenges in meeting such food production. The production of a plant type is not independent of its growth and development processes, which in this case are affected by two factors, namely internal and external factors. Internal factors are properties contained in the material or seed of the plant. Whereas external factors are factors located around those plants. One internal factor is the variety of a plant and one of the external factors is the radiation of solar light affecting plant growth.The study has a goal of knowing the efficiency of solar radiation (EPR) of two superior rice varieties at various levels of N concentration in tidal lands.Research was implemented at UPT Seed Hall of Right Pond Village Food Crops, Barambai District of Barito Kuala County from March 2018 to with July 2018. The treatment design used is the Shareless Shape Draft (Split plot design) with the main factor (main plot) is 5 Nitrogen fertilization rates which are n1 = 75 kg N ha-1 (187.5 kg urea ha-1) n2 = 150 kg ha-1 (375 kg urea ha-1) n3= 225 kg N ha-1 (562.5 kg urea ha-1)n 4 = 300 kg N ha-1 (750 kg urea ha-1) n5= 375 kg N ha-1 (937.5 kg urea ha-1) and second factor (sub-plot) is 2 varieties of rice that are v1 = IPB 3S and v2 = IPB Batola 6R, while the environmental design used is RAK (Group Random Design). The intensity of solar light at the time of transplanting is 612.2 cal/cm2/day. The intensity of solar light at the time of initiation of the mallai is 599.5 cal/cm2/day. The intensity of solar light at the time of anthesis is 772.7 cal/cm2/day. The total solar light intensity that plants require since transplanting until harvest is 2896.1 cal/cm2/day. Variety analysis suggests that EPR has an effect on the single factor of varieties can be known that is from the EPR value of each variety. The higher the value of EPR it can be known the ability of plants in converting energy into biomass the better, after advanced tests it is known the value of EPR of each variety. IPB 3S varieties are more efficient at capturing or converting solar light with an EPR value of (2.1305) compared to Batola 6R GPA of (2.0918).